Early rheumatoid arthritis: a prospective study on how to induce the remission - S. Zingarelli; M. Filippini; C. Bazzani; T. Ziglioli; A. Giugno; R. Gorla (PAGEPress Publications, 2011)
Objectives: To investigate whether the aggressive use of DMARDs can control the clinical disease in the early arthritis, to define new parameters of the disease aggressivity and to study the effectiveness of RMN in comparison with RX focusing on the articular erosions. Methods: 45 patients having a case of early arthritis (less 6 months) with 3 or more swollen joints were recruited and treated with 80 mg of steroids in order to distinguish persistent arthritis from non persistent ones. Afterward we began to use DMARDs with persistent arthritis and, if it wasn't helpful, we shifted to anti-TNFα therapy. The clinical response was valued by SDAI. Results: After 1 year our therapeutic approach showed a remission in 60% of the patients. The 82% of remaining obtained a significant SDAI improvement and only in 3 cases we used anti-TNFα due to a persistent high disease activity. Anti-CCp were positive in 46% of patients in remission and in 53% of the rest. The bone erosions were present in 4 patients only and they were detected by RMN, only 2 by RX. Conclusions: We observed a clinical remission in the 60% of patients treated with aggressive DMARDs. During our trial, anti-CCp weren't predictive about the therapy response. We observed that RMN is more effective than RX in detecting erosions and it's necessary for diagnosis and follow-up of early arthritis.